Analyzing the Effect of Unemployment and Growth Nexus in Nigeria - Dr. HUSSAIN A. Abubakar; Niyi Jacob Ogunode (International Journal on Integrated Education, 2023)
This study analyzed the effect of unemployment nexus on economic growth in Nigeria. The study used time series data front between 19812017.UH Real Gross Domestic Product (GDP) is proxy for growth with inflation and savings deposit as the independent variables. The researcher used an error correction model (ECM) estimation technique in. analyzing data that were sourced from National Bureau of Statistics and Central Bank of Nigeria statistical bulletin. Stationarity test, cointegration test and error correction mechanism were carried .out to avoid possible spurious regression, the rese/archer found inverse and insignificant relationship between Unemployment and Real. Gross Domestic Product (RGDP). Furthermore, positive and insignificant relationship was established between Savings Deposits and Real Gross Domestic Product (RGDP). Inflation has negative but insignificant, relationship with RGDP. The study recommended that government should profile the unemployed youths into skilled and unskilled labour and target its poverty reduction job policies toward reducing the employment rate for economic prosperity.